2014
DOI: 10.3390/molecules190915258
|View full text |Cite
|
Sign up to set email alerts
|

Current and Potential Applications of Bismuth-Based Drugs

Abstract: : Bismuth compounds have been used extensively as medicines and in particular for the treatment of gastrointestinal ailments. In addition to bismuth's well known gastroprotective effects and efficacy in treating H. pylori infection it also has broad anti-microbial, anti-leishmanial and anti-cancer properties. Aspects of the biological chemistry of bismuth are discussed and biomolecular targets associated with bismuth treatment are highlighted. This review strives to provide the reader with an up to date accoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
86
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(102 citation statements)
references
References 130 publications
(259 reference statements)
0
86
0
5
Order By: Relevance
“…[1,2] In particular platinum (Pt) drugs such as cisplatin, carboplatin and oxaliplatin, Figure 1, have played a very important and well documented role in treating cancer and are employed in nearly 50% of anti-cancer regimens. [3] …”
Section: Introductionmentioning
confidence: 99%
“…[1,2] In particular platinum (Pt) drugs such as cisplatin, carboplatin and oxaliplatin, Figure 1, have played a very important and well documented role in treating cancer and are employed in nearly 50% of anti-cancer regimens. [3] …”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it possess antibacterial effects by inhibiting various enzymes produced by H. py Data are presented as n (%) with 95% CI. See Table 1 lori (including urease, catalase, and lipase/phospholipase), preventing adhesion of H. pylori to surface epithelial cells, and inhibiting ATP synthesis and some membrane functions in H. pylori [20][21][22]. It has been reported that the addition of bismuth to standard triple therapy improved the eradication rate [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…Bismuth (Z=83) has been used for over 100 years as an over-the-counter remedy for gastrointestinal problems[144]. Bismuth has the highest K-edge energy (91 keV) of all the elements under consideration and as a result, it shows less change in CT number across different kVp settings compared to iodine and barium.…”
Section: Choice Of Elements For Spectral Ct Contrast Materialsmentioning
confidence: 99%